PEMAHAMAN SISWA TERHADAP MATERI TEKS DESKRIPSI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN SNOWBALL THROWING PADA SISWA KELAS VII A SMP - Mallma Fatimah Al Tanjung; Dida Firmansyah (IKIP Siliwangi, 2019)
Lack of student learning outcomes and student understanding of the material that has been delivered by the teacher is influenced by the inactivity of students when the learning process takes place, activeness of students can have a positive impact on memory, students always write a text that does not pay attention to elements, structures and some that do not the meaning of the description text itself because of a lack of understanding of the material before they practice writing. Teachers must be good at choosing a model or method that will be used when learning takes place, one of which is the Snowball Throwing learning model. This research was conducted to find out 1) whether there was a positive effect that resulted from the Snowball Throwing method. 2) how students respond after the Snowball Throwing model is applied to learning. 3) how much increase in learning outcomes and student activity after the Snowball Throwing model is applied. This study uses a qualitative approach, data obtained from the results of the pretest and posttest with interview, observation, and test techniques. The results of this study are Snowball Throwing learning models can improve material understanding and activeness of students in the class, with a very good response and have a positive influence on students.